The Influence of Cooperative Learning Models of Think Pair Share Types and Social Attitudes towards Learning Outcomes Theme of Deliberation in the Contents of Learning of Student Citizenship Education in Class V of Medan Experimental SDN - Masjuliana Saragih; Yusnadi Yusnadi; Alesyanti Alesyanti (Budapest International Research and Critics University, 2020)
This research is motivated by the low learning outcomes of the topic of learning about Citizenship Education in the SD Negeri Experimental District in Medan. The aim of this study was to find out how the Think Pair cooperative learning model works. To determine the effect of the social attitudes of the students; Identify the interaction between Think Pair Share collaborative learning models and social attitudes and their impact on learning outcomes. This study uses quasi-experimental research methods. The study population consisted of all fifth grade students of SD Negeri Experiment Medan, which consisted of 60 people in two classes. The experimental class received a cooperative learning model of the type Think Pair Share and the control class a conventional learning models. The results of the study show that: (1) the Think Pair Share Learning Model has an impact on learning outcomes. This is evident from the ANAVA results of an increase in Citizenship Education learning outcomes, which averaged 91.97 in the experimental class, above the average of the control class of 70.37. (2) The influence of social attitudes on learning outcomes. From the ANAVA results it can be seen that the average civilian learning outcomes with social attitudes are 80.61 higher than the control class 76.81, while the social attitudes in the experimental class are low. (3) Interaction between Think-Pair-Share cooperative learning models and social attitudes and their impact on learning outcomes. It can be said that the higher the social attitudes, the higher the learning outcomes achieved. Conversely, the lower the social attitudes, the lower the learning outcomes achieved.